1960
DOI: 10.1346/ccmn.1960.0090107
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Status of Clay Systems

Abstract: Illite and montmoriUonite have been compressed into cores under a pressure of 1200 arm. The structural status of these clays has been examined by means of detailed nitrogen adsorption-desorption isotherms and by means of electron micrographs of fracture surfaces of the clay cores. The subsequent swelling behavior of sodium and calcium clay cores has been analyzed in terms of the model derived from these measurements and the specific surface area of the clay. A generalized theory for the condensation of plate-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1968
1968
2007
2007

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…Some parallel condensation of the Ca-illite particles to form domains may exist (Aylmore and Quirk, 1962). This phenomenon is unlikely even for Cs-illite inasmuch as Greene et al (1978) were not able to obtain evidence for domain formation in Ca-illite suspensions.…”
Section: Particle Condensationmentioning
confidence: 98%
“…Some parallel condensation of the Ca-illite particles to form domains may exist (Aylmore and Quirk, 1962). This phenomenon is unlikely even for Cs-illite inasmuch as Greene et al (1978) were not able to obtain evidence for domain formation in Ca-illite suspensions.…”
Section: Particle Condensationmentioning
confidence: 98%
“…Ca-montmorillonite, for example, does not swell to the same extent as Namontmorillonite [26,27]. Illite crystals, unlike montmorillonite, do not swell appreciably [28]. Hence swelling in illitic material due to the uptake of water results from the separation of crystals themselves i.e.…”
Section: Swelling Clay-c-s-h Analogues For Expansive Behaviormentioning
confidence: 99%
“…Aylmore and Quirk (1962) reported that the swelling of Ca-illite was insensitive to electrolyte concentration over the range from 4 M to distilled water. They attributed this limited intercrystalline swelling to the existence of a potential m i n i m u m between the contiguous clay crystals in an assemblage of near-parallel, aligned clay particles, described as a domain.…”
Section: Introductionmentioning
confidence: 99%